Numerically simulating the interconnected nature of the road-soil-pipe infrastructure - Reza Movahedifar; Alexander Royal; Mehran Eskandari Torbaghan; Nicole Metje; David Chapman (Results in Engineering, 2024)
Successful operation of infrastructure, such as the road, rail, and utility networks, are fundamental to modern living, and failure of these can have significant consequences. Yet they are likely, when in proximity, to interact, and failure of one can cause cascade failure of others. Equally, all are supported by the ground, which can also experience changes in properties as the infrastructure deteriorates. Research into the interconnected nature of these infrastructure is not new, but much focuses on the structural behaviour of the human-made components (road structures, pipes, etc). This paper presents a numerical model developed to systematically evaluate the impacts of simulated pipe leakage on the surrounding ground and pavement layer above. The model outputs indicate that the road surface experiences increased strains due to weakening ground conditions around the leaking pipe and these are exacerbated by asymmetrical traffic loading. Findings indicate that leakage can cause differential settlements (observed both at the surface and pipe levels), which could cause localised deterioration of the pavement material (due to tensile cracking, etc.) precipitating surface anomalies like cracks or potholes. This suggests that understanding the root-cause of road surface deterioration is critical to efficient long-term management of road networks so that the symptoms are not remediated whilst the root-cause remains. This research provides a crucial step towards enhancing predictive maintenance and calls for further investigation into the long-term geotechnical impacts of leakage, to develop robust repair and maintenance frameworks that address underlying causes of road surface anomalies.